Just keep doing what you did in 1. I'll show you how easy it is.
2.
a) g(9) = 9 - 5 / 2 = 4 / 2 = 2.
b) g(0) = 0 - 5 / 2 = 5 / 2 = 2 1 / 2.
c) g(3) = 3 - 5 / 2 = 2 / 2 = 1.
d) g(17) = 17 - 5 / 2 = 12 / 2 = 6.
3.
a) f(3) = 3^2 - 4 = 9 - 5 = 4.
b) f(-4) = -4^2 - 4 = 16 - 4 = 12.
c) f(0) = 0^2 - 4 = 0 - 4 = -4.
d) f(-2) = -2^2 - 4 = 4 - 4 = 0.
4.
a) f(10) = 10 / 2 - 6 = 5 - 6 = -1; -1 is the solution.
5.
a) I'll test one after another.
1. f(0) = 2(0) - 3 = 0 - 3 = -3 > g(0) = 3(0) / 2 + 1 = 0 + 1 = 1; this is incorrect.
2. f(2) = 2(2) - 3 = 4 - 3 = 1 = g(2) = 3(2) / 2 + 1 = 6 / 2 + 1 = 3 + 1 = 4; this is incorrect.
3. f(8) = 2(8) - 3 = 16 - 3 = 13 = g(8) = 3(8) / 2 + 1 = 24 / 2 + 1 = 12 + 1 = 13; this is correct.
4. g(4) = 3(4) / 2 + 1 = 12 / 2 + 1 = 6 + 1 = 7 < f(4) = 2(4) - 3 = 8 - 3 = 5; this is incorrect.
Hope this helps :)